On the Statically Equivalent Loads in Sainit Venant’s Principle - Sokołowski, M. (Engineering Transactions, 1988)
In traditional Saint Venant’s principle formulations the loads leading to similar stress distributions are assumed to be statically equivalent, i.e. to yield identical resultant forces and moments. It is shown that this requirement may be replaced with a more general one according to which the first N+1 moments of order 0,1, ..., N of both loading systems should be compared. In the case of an elastic half-plane loaded at the boundary it is shown that the resulting stress differences calculated at large distances from the loaded region are of the order of kr-N - 2 where N denotes the highest order of identical moments of two loading systems, and r - distance from the loaded region.